Effect of Student-Centered Teaching Approach on Academic Performance in Mathematics at the Secondary School Level - Islam, Md Sefatul; Sarker , Md Shakil; Abir, Shahriar Shajid; Kamal , Fairuz (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The study's primary purpose is to investigate the effect of a Student-Centered Teaching Approach on Student's Academic Performance in Mathematics at the Secondary Level. Method: The study was carried out using the quasi-experiment method. In this study, convenient sampling was used to select secondary schools and select students for intervention. This study used a few instrumentations, such as a mathematics test, which was used for pre-and posttests. Results: The analysis data in the posttest reveal an increase in mean, mode, and median scores after implementing a student-centered approach toward the experimental group. This study proves that the effectiveness of a student-centered teaching approach positively impacts students' academic performance in mathematics. The rejection of the null hypothesis suggests that the student-centered approach led to a statistically significant improvement in students' scores compared to the teacher-centered approach. Novelty: This contributes valuable insights to educational practices, advocating for adopting student-centered methods in mathematics instruction. This study proved the effectiveness of the Student-Centered Teaching Approach on students's Academic Performance in Mathematics at the Secondary Level.